Effects of phase noise on digital modulation schemes in a slowly fading environment - Zhang, Yunjun. (2009)
The effects of random phase noise on the performance of several different digital modulation schemes transmitted over AWGN, slowly flat fading Rayleigh and Rician channels are examined. The modulation schemes considered are BPSK, QPSK, BFSK and binary DPSK.